Nauka w języku niemieckim w polskich placówkach oświatowych w świetle zobowiązań wynikających z Europejskiej Karty języków regionalnych lub mniejszościowych - Siejak, Paweł (Ius et Administratio, 2016)
This article reviews German minority in Poland. The first part of the paper brings a long and difficalt history of relations between the people of Poland and Germany in 20th century on Polish territories. The present mentality both nations was created by the historical facts, particularly from 20th century. The tragic history of the Second World War – persecutions and extermination of Polish nation were recalled here. Nonetheless resettlements of the Germans from Lower Silesia, Warmia, Mazuria Lake District and Pomerania took place after the end of the Second World War. This article says about the hard period of existance of the Germans in Polish People’s Republic until 1989 and during democratic transformations in Central Europe. The second problem the author recounted was the system of protection the rights of national minorities relied in Polish People’s Republic until 1990. Special attention was devoted to a great deal of the legal interial acts, for example the law about foreigners. The author emphasized the significance of Polish and German Treaty which refered to good relations between these two countries. Nonetheless, the author underlined the importance of the institutions and international organizations which increase on the position of the Germans in Poland (the United Nations, European Union, Organization for Security and Co-operation in Europe with High Commissioner on National Minorities, and above all Council of Europe with Charter of Regional or Minority Languages and the Framework Convention for the Protection of National Minorities). In conclusion the author elaborated the prezent problem of teaching German language the people of Germany in Poland and contained an extensive analysis of this problem from perspective of norms of Council of Europe and Polish agreements when our country became a party of Charter of Regional or Minarity Languages.